Growth and survival of Hippocampus barbouri (Jordan & Richardson, 1908) and Hippocampus kuda (Bleeker, 1852) fed with artemia of different enrichments - Len, Yung Wung (2019)
Seahorses from the genus Hippocampus are facing tremendous pressure due to over exploitation to satisfy the demand for traditional Chinese medicine and ornamental fish trade. Hippocampus barbouri and Hippocampus kuda among the seahorse species being heavily traded in Malaysia and Thailand respectively. The establishment of seahorse aquaculture for sustainable supply is imminent in order to prevent the extinction of the species. Seahorse is one of the most sensitive fish species, thus every aspects relate to its growth and survival must be studied thoroughly. Among all, feeding aspect is the most critical. Artemia sp. is commonly used as live food in the culture of marine fish. However, this zooplankton become less nutritious as it grows, therefore requires enrichment. Suitable enrichment will contribute to growth and survival, specifically during early juvenile stage. This study focused on two main species of seahorses, H. barbouri and H. kuda. Experiments were carried out at two different locations, Hatchery unit, Institute of Bioscience, Universiti Putra Malaysia, Serdang, Selangor, Malaysia for H. barbouri, while at Training Unit, Faculty of Fisheries, Kasetsart University, Bangkok, Thailand, for H. kuda. The objectives of this study were divided into two main parts. First, to estimate the amount of Artemia nauplii consumed by seahorses from newborn to juvenile. While adult Artemia was used as food for juvenile to adult stage. Second objective was conducted to compare the growth and survival of seahorse juveniles fed with Artemia enriched with different enrichments. This research consist of five experimental studies in total. First two feeding experiments utilized Artemia nauplii for the feeding of newborn to early juvenile stage for the two seahorse species. The third feeding experiment estimates the amount of adult Artemia consumed by adult H. barbouri with age of 120 to 300 day after birth (DAB). Finally, the last two feeding experiments were conducted on H. barbouri and H. kuda juveniles using Artemia metanauplii enriched with different enrichments. Results of the Artemia consumption experiments for H. barbouri and H. kuda, showed increasing numbers of Artemia nauplii consumed for both species. As the age of seahorses increase, the amount of Artemia nauplii consumed also increase. Upon reaching the early juvenile stage of 42 DAB, H. kuda with the height of 32.32±1.23 mm consumed 28-39 Artemia nauplii per feeding. In comparison, H. barbouri at 28 DAB with height of 32.51±1.28 mm were able to consume 27-42 Artemia nauplii per feeding, similar to the amount consumed by 42 DAB H. kuda. As for the average numbers of adult Artemia consumed by H. barbouri, increasing consumption trend was observed as the age increased. The average numbers of adult Artemia consumed at the age of 120, 150, 180, 210, 240, 270, and 300 DAB were 32, 34, 47, 59, 55, 63 and 64 Artemia/feeding respectively. Results from the 60 days feeding experiment showed significantly higher (P<0.05) in height of H. barbouri juveniles when fed with Artemia only, Artemia enriched with pellet, and with Spirulina sp. as compared to Artemia enriched with fresh Chlorella sp. and Chlorella sp. powder. Survival of H. barbouri was significantly higher (P<0.05) when fed with Artemia enriched with fresh Chlorella sp., pellet and Chlorella sp. powder. As for the feeding experiment on H. kuda, no significant different (P>0.05) was observed for the height, weight and survival of juveniles when fed with Artemia enriched with pellet and with SELCO emulsion (A1 DHA SELCO). Based on the findings of this study, it can be concluded that the Artemia nauplii can be used as diet to support growth and survival of H. barbouri and H. kuda from newborn to juvenile stage. Simple feeding enrichment using pellet on Artemia may be more cost effective as compared to other enrichments. As for water quality, H. barbouri and H. kuda juveniles have similar water parameters tolerance. Recommended dissolved oxygen (DO) should be above 4.2 mg/L, with temperature range of 26.5 to 30°C, pH of 7.4 to 8.0, ammonia below 0.25 mg/L and salinity between 26 to 35 psu for the successful culture of H. barbouri and H. kuda juveniles.